(untitled) (Fiep Bulletin - online, 2014)
OBJECTIVE: To verify the benefits of a program of resisted training associated to the pharmacological treatment in senior with arterial hipertension of the program "Feli(z)Idade". METHOD: 21 were researched senior of both sexes being 17 women and 4 men that attended the institutional project FELI(Z)IDADE promoted by University of Biomedical Sciences of Cacoal (FACIMED) with average of age 64,14 ± 2,59. The research was of experimental descriptive character, through the quantitative method, being used the convenience technique for the selection of the sample. The data were collected by adapted questionnaires and validated, IMC, percentile of fat and waist circumference and test of maximum repetitions. The tabulation was done by an average with standard deviation with test t of Studant, and wilcoxon test for two samples related with significance of p <0,05. The data were analyzed by the laboratory of epidemiology of FACIMED (FACIEPI). RESULTS: 57,1% attend the school for four years, 71,4% never smoked and 95,5% don’t make weekly alcoholic ingestion, 85,7% consume fries, 34,2% ingest diuretic daily, 57,1% feel therir life is empty. IMC female pre 30,04±6,09 after31,2±5,27 for men IMC pre 27,1±4,11 after 23,9±2,9 in relation to the systolic blood pressure in the 1st week the average physical pre-training was of 134,3 mmHg and aftertraining of 144 mmHg, already in the 8th week of training the average pre-training was 126,5 mmHg and after-training 121,7 mmHg, and the blood pressure diastolic 1st week the average pre-training was of 83,9 mmHg and after-training of 90,7 mmHg, already in the 8th week of the average pre-training it was 81,9 mmHg and after-training 79 mmHg. CONCLUSION: It was possible to conclude that there are evidences of physiologic benefits, sharp hypotension, with the intervention of the resisted training and the pharmacological treatment in the studied seniors with hipertension.